Public holiday usage of the medical library: a survey - Sinnasamy, J. (University of Malaya Library, 1997)
Descrices briefly a short survey carried out durin three public holidays to find out why users were using the library despite the public holidays. A one page questionnaire were distribued at the entrance of the library. The results indicate tha the library plays an importan role in providing a place to read and borrow open-shelf books. The majority came to read newspapers.